Profitability and technical efficiency of Binadhan-17 cultivation in the Haor areas of Bangladesh - Islam, Syful; Rahman, Md Habibur; Rashidul Haque, Mohammad; Sarkar, Md Mohsin Ali; Sultana, Razia (Asian-Australasian Journal of Food Safety and Security, 2024)
The Haor region contributes approximately 20% of Bangladesh’s total rice production, and this study focused on the Binadhan-17 rice variety in three key Haor districts including, Sunamganj, Kishoreganj, and Netrokona. The research aimed to assess the costs, returns, and technical efficiency of Binadhan-17 cultivation, surveying 180 randomly selected farmers from the region. Using a stochastic frontier production function model and descriptive statistics, the study found that the average production cost per hectare was BDT 76,863, with fixed costs accounting for 35.90% and variable costs for 64.10%. The average net return per hectare was BDT 44,289, and the Benefit-Cost Ratio (BCR) was 1.58, with Sunamganj having the highest BCR (1.62), followed by Kishoreganj (1.57) and Netrokona (1.54). Significant positive relationships were found between human labor, land preparation, and insecticide costs at the 1% level, while seed, urea, and organic manure costs were significant at the 10% level, and TSP was significant at the 5% level. Around 68.33% of farmers achieved outputs close to the maximum frontier level (91%–99%), with an average technical efficiency of 89.40%, indicating a 10.60% production loss due to inefficiency. The study also identified several challenges faced by farmers, including difficulties in obtaining timely seed and labor, limited knowledge of production technologies, high fertilizer prices, and lack of capital, offering insights for policymakers to enhance rice production in the short term. Asian Australas. J. Food Saf. Secur. 2024, 8(2), 58-66